ANALYSIS AN EXTRA-HIGH VOLTAGE TRANSMISSION LINE INTEGRATED WITH ZIGBEE SENSOR NETWORK - Pakka, Hariani Ma'tang; Masa, M. Anas; Syarifuddin, Andi; Al Ghamdi, Ahmed Saeed; Suyuti, Saidah (Transmisi: Jurnal Ilmiah Teknik Elektro, 2025)
The abundance and variety of sensor nodes in intelligent transmission lines make them unique and distinguishable. These nodes are essential components of the system, providing valuable data and information that enable efficient and effective communication. Intelligent transmission lines are characterized by their abundance and diverse range of sensor nodes. Comparing and analyzing performance metrics for star, tree, and mesh networks with the same attribute configuration includes application layer end-to-end latency and MAC layer throughput. By utilizing the ZigBee protocol in conjunction with OPNET, this is accomplished via the modeling and simulation of a wireless sensor network structure for intelligent transmission lines. An extra-high voltage transmission line that integrates multiple embedded sensing nodes was equipped with an appropriate ZigBee wireless network architecture. Following the integration of the tower's scenarios and results simulation of OPNET, the compatibility between mesh and ZigBee wireless network topology of the transmission lines, comprising several embedded sensing nodes, has been confirmed.